2016
DOI: 10.1007/s00145-016-9239-3
|View full text |Cite
|
Sign up to set email alerts
|

From Private Simultaneous Messages to Zero-Information Arthur–Merlin Protocols and Back

Abstract: Göös, Pitassi and Watson (ITCS, 2015) have recently introduced the notion of Zero-Information Arthur-Merlin Protocols (ZAM). In this model, which can be viewed as a private version of the standard Arthur-Merlin communication complexity game, Alice and Bob are holding a pair of inputs x and y respectively, and Merlin, the prover, attempts to convince them that some public function f evaluates to 1 on (x, y). In addition to standard completeness and soundness, Göös et al., require a "zero-knowledge" property whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…While most of our focus has been on showing that hardness in SZK and NP ∩ coNP does not follow from cryptography, here we ask the "inverse question", namely whether certain cryptographic primitives can be built from other cryptographic primitives together with hardness in certain structured complexity classes. Little is known in this direction with the exception of the beautiful work of Ostrovsky and Wigderson [OW93a] who construct a OWF from average-case SZK-hardness, and the recent work of Applebaum and Raykov [AR16] who showed that average-case hardness in the subclass PRE ⊆ SRE ⊆ SZK of languages with a perfect randomized encoding gives us collision-resistant hashing.…”
Section: Corollary 14 (From [Sw14 Wat15] Informal)mentioning
confidence: 99%
“…While most of our focus has been on showing that hardness in SZK and NP ∩ coNP does not follow from cryptography, here we ask the "inverse question", namely whether certain cryptographic primitives can be built from other cryptographic primitives together with hardness in certain structured complexity classes. Little is known in this direction with the exception of the beautiful work of Ostrovsky and Wigderson [OW93a] who construct a OWF from average-case SZK-hardness, and the recent work of Applebaum and Raykov [AR16] who showed that average-case hardness in the subclass PRE ⊆ SRE ⊆ SZK of languages with a perfect randomized encoding gives us collision-resistant hashing.…”
Section: Corollary 14 (From [Sw14 Wat15] Informal)mentioning
confidence: 99%